Investigating the basis of competitive nodulation and bacteroid development in Rhizobium leguminosarum - Ford, BL (2021)
Some soil-dwelling bacteria in the genus Rhizobium can form symbioses with leguminous plants, including important crop species such as peas and beans. During symbiosis, rhizobial bacteroids inhabiting root nodules fix atmospheric dinitrogen into ammonium, which is exchanged with the host plant for fixed carbon from photosynthesis. Inoculation of leguminous crops with highly effective rhizobia can significantly increase crop yields and reduce inorganic fertiliser usage. However, potential yield benefits are reduced or lost if inoculant strains are unable to compete with indigenous rhizobia.